Fostering reading interest through digital storytelling for young learners in the early childhood - Siane Indriani; Hanna Suteja (Intelektual Pustaka Media Utama, 2023)
Children in the digital era are exposed to the advancement of information technology and multimedia that might bring both positive and negative influence toward their development. During early childhood, children are using mostly their senses to explore the world around them, including learning some values from the story books exposed to them. However, parents or family do not give optimal support in the children’s learning process. Therefore, it is a challenge for English language teaching (ELT) pre-service teachers in implementing a digital storytelling to engage the children with the learning material and creative ways to optimally utilize technology, but at the same time give a comprehensive support for children to improve their English skills as well as the embedded values within the stories. The present study aims to reveal the opportunities and challenges in fostering a child’s reading interest through digital storytelling. All the details were recorded through observations, responses from the children while they were watching the digital story, and a daily journal written by ELT pre-service teacher. From the result, it was found that through their interactions with the stories, children were exposed by the values embedded, furthermore, their reading interest is developing where more optimal support from the parents or caregivers is urgently needed.